Meningkatkan Kesadaran Masyarakat tentang Manfaat Tanaman Jahe sebagai Investasi Produktif dalam Bisnis - Chaeru Syahru Ramdani; Adi Sofyana Latif; Lia Ira Sahara; Rananda Septanta (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This community service (PKM) activity was conducted to address the limited public awareness regarding the economic and health benefits of ginger plants, particularly as a productive investment opportunity. Ginger, as a widely available medicinal plant, has significant potential to be developed into a sustainable small-scale business. Therefore, this program aimed to increase community understanding and motivation to utilize ginger cultivation as a source of income and entrepreneurship. The PKM was carried out at the Pamulang Orphanage Foundation, South Tangerang, on April 18, 2026. The activity involved six lecturers from Pamulang University and was attended by 26 participants, consisting of children and teachers. The implementation methods included material presentation, hands-on practice, interactive discussions, and question-and-answer sessions. The program was conducted in three stages: preparation, implementation, and reporting. The results showed a significant increase in participants’ knowledge and interest in ginger cultivation and its economic value. Participants were actively engaged and demonstrated enthusiasm during practical sessions. They gained insights into simple cultivation techniques and business opportunities related to ginger-based products. In conclusion, this PKM activity successfully enhanced community awareness and provided practical knowledge on utilizing ginger as a productive investment.